Lawsonia inermis extract: Antibacterial, anticancer and antioxidant properties - S. Revathi; E. K. Nasser; H. K. Wafaa; A. B. Altemimi; S. Sutikno; T. Kartika; I. Guswenrivo; F. H. Awlqadr; T. G. Abedelmaksoud (Пищевые системы, 2025)
Henna, scientifically known as Lawsonia inermis, is long used for its therapeutic benefits in several civilisations. This study examines the antibacterial, anticancer, and antioxidant properties of the leaf extract from L. inermis. The phytochemical study indicated the existence of alkaloids, flavonoids, glycosides, phenolic compounds, and tannins. GC–Mass Spectrometry detected notable bioactive chemicals, including tetracosamethyl-cyclododecasiloxane and cyclohexasiloxane. The extracts demonstrated strong antioxidant properties, as evidenced by their values of 254.32 and 121.25%, as well as their high FRAP values, demonstrating their effective ability to scavenge radicals. The antibacterial effectiveness, assessed by the disc-diffusion technique, demonstrated substantial inhibition zones against both Gram positive and Gram-negative microorganisms. The MTT experiment exhibited significant anticancer efficacy against MCF‑7 breast cancer cell lines, with an IC50 value of 1.682 μg/mL. The results indicate that extracts from L. inermis contain significant bioactive substances that have the potential to be utilised in the development of innovative medications aimed at addressing oxidative stress, bacterial infections, and cancer.